Asuhan Keperawatan pada Ny. M dengan Gangguan Sistem Muskuloskeletal: Pre Operasi Fraktur Collum Femur Dextra di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Anisa Nurul Adila; Ahmad Zakiudin; Yusriani Saleh Baso (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
According to WHO in 2020, the incidence of fractures was reported, with more than 13 million cases and a prevalence rate of 2.7%. Based on medical record data from RSUD dr. Soeselo, Tegal Regency, in 2023 the number of femoral neck fracture patients will be 129 people (1.34%). Femoral neck fractures usually require operative therapy rather than conservative therapy. The aim of this scientific paper is to provide nursing care to preoperative patients with femoral neck fractures at RSUD dr. Soeselo, Tegal Regency. The results of the assessment showed that the patient experienced pain in the upper right thigh, traction weighing 5 kg was applied. Nursing problems in this final scientific work include acute pain, anxiety and impaired physical mobility.